Executive compensation and earnings management - LU, XIAOQIU (2017)
Abstract This paper aims to estimate the relationship between incentive-based executive pay and earnings management. It focuses on a sample of public companies listed on the NASDAQ Stock Market, over a period from 2008 to 2016. Based on prior accounting research, this study applies the Jones model to estimates the fixed-effects panel date model, and the research results show that bonuses are negatively correlated to earnings management, which implies that the agency problem can be mitigated through the design of CEO compensation packages. In addition, this paper finds that stock-based compensation has a positive impact on earnings manipulation, indicating that it needs careful consideration of the potential good and bad effects when companies make the use of high-powered incentives to motivate executives to maximise the value of companies. In this case, the monitoring departments should pay more attention to the quality of financial reports. Keywords: Executive compensation, Earnings management, Bonuses, Stock options